José Gurvich (1927-1974) óleos, témperas, acuarelas, dibujos, esculturas, grabados, ediciones limitadas : oils, temperas, watercolors, drawings, sculptures, etchings, limited editions : 15 Agosto-30 Setiembre 2018 Montevideo, Uruguay, October 4th-October 31st 2018 Washington D.C, U.S.A, December 5th-December 9th 2018 Miami, U.S.A - Sullivan, Edward J. 1949-; Peluffo Linari, Gabriel 1946- (Museo Gurvich, 2018)
Jose Gurvich (b. Uruguay 1927-1974) immigrated from Germany in 1932. Bilingual Spanish / English catalog of the exhibition by Jose Gurvich (1927-1974), Uruguayan painter, draftsman, sculptor and writer, containing oil paintings, tempera paints, watercolors, drawings, sculptures, engravings and limited editions, held in the Salon de Arts of the Embassy of Uruguay in Washington DC Includes brief preliminary studies of his work by Gabriel Peluffo Linari and Edward J. Sullivan
Catalog of an exhibition held at al Sur, Montevideo, August 15 - September 30, 2018, Embassy of Uruguay, Washington, DC, October 4 - 31, 2018, and Pinta Miami, Miami, December 5 - 9, 2018
Keywords: Gurvich, José -- 1927-1974; Gurvich, José / 1927-1974 / Exhibitions; Gurvich, José / 1927-1974; Art, Uruguayan / 20th century / Exhibitions; Art, Uruguayan; 1900-1999; Ausstellungskatalog -- Galería Al Sur -- 15.08.2018-30.09.2018 -- Montevideo; Ausstellungskatalog -- United States, Embassy of Uruguay -- 04.10.2018-31.10.2018 -- Washington, DC; Ausstellungskatalog -- Pinta -- 05.12.2018-09.12.2018 -- Miami, Fla.; Bildband